RNA-template dependent de novo telomere addition. Issue 8 (2nd August 2016) - Fuhrmann, Gloria; Jönsson, Franziska; Weil, Patrick Philipp; Postberg, Jan; Lipps, Hans J.
Abstract: De novo addition of telomeric sequences can occur at broken chromosomes and must be well controlled, which is essential during programmed DNA reorganization processes. In ciliated protozoa an extreme form of DNA-reorganization is observed during macronuclear differentiation after sexual reproduction leading to the elimination of specific parts of the germline genome. Regulating these processes involves small noncoding RNAs, but in addition DNA-reordering, excision and amplification require RNA templates deriving from the parental macronucleus. We show that these putative RNA templates can carry telomeric repeats. Microinjection of RNA templates carrying modified telomeres into the developing macronucleus leads to modified telomeres in vegetative cells, providing strong evidence, that de novo addition of telomeres depends on a telomere-containing transcript from the parental macronucleus.